Clinical practice recommendations on the management of perioperative cardiac arrest: A report from the PERIOPCA Consortium - Chalkias, Athanasios; Mongardon, Nicolas; Boboshko, Vladimir; Cerny, Vladimir; Constant, Anne-Laure; De Roux, Quentin; Finco, Gabriele; Fumagalli, Francesca; Gkamprela, Eleana; Legriel, Stéphane; Lomivorotov, Vladimir; Magliocca, Aurora; et al. (Critical care (London, England), 2021)
BACKGROUND: Perioperative cardiac arrest is a rare complication with an incidence of around 1 in 1400 cases, but it carries a high burden of mortality reaching up to 70% at 30 days. Despite its specificities, guidelines for treatment of perioperative cardiac arrest are lacking. Gathering the available literature may improve quality of care and outcome of patients. METHODS: The PERIOPCA Task Force identified major clinical questions about the management of perioperative cardiac arrest and framed them into the therapy population [P], intervention [I], comparator [C], and outcome [O] (PICO) format. Systematic searches of PubMed, Embase, and the Cochrane Library for articles published until September 2020 were performed. Consensus-based treatment recommendations were created using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) system. The strength of consensus among the Task Force members about the recommendations was assessed through a modified Delphi consensus process. RESULTS: Twenty-two PICO questions were addressed, and the recommendations were validated in two Delphi rounds. A summary of evidence for each outcome is reported and accompanied by an overall assessment of the evidence to guide healthcare providers. CONCLUSIONS: The main limitations of our work lie in the scarcity of good quality evidence on this topic. Still, these recommendations provide a basis for decision making, as well as a guide for future research on perioperative cardiac arrest.
Keywords: delfská metoda; Perioperative Period; Resuscitation; konsensus; srdeční zástava; perioperační období; Consensus; Humans; Heart Arrest; lidé; Cardiac arrest; PERIOPCA; Delphi Technique; Perioperative